Treatment of renovascular hypertension by renal revascularization by venous graft - Danza, Rómulo; Pollero, Héctor; Arias, José; Danza, Franco; Pravia, Juan; Suárez, Raúl (Cirugía del Uruguay, 1973)
A) Case material consists of three patients with reno-vascular hypertension, who wese treated by venous graft from the aorta to the renal artery distal to occlusion. Post-operatory evolution !asted between 18 and 14 monts. B) One of the abovementioned cases was due to congenital stenosis, another to fibromuscular hyperplasia and the third to arteriosclerosis. C) All cases had had long evolution, over 6 years. D) The three patients were studied by post-operatory arteriography which showed bood functioning of graft. E) In two cases tension figures became normal; the remaining one showed marked improvement of bypertension but did not reach normal values. F) Pathological and diagnostica! elements on which the surgical treatment as based are discussed. Stress is laid on the interest of such procedurz since it can cure hyperte1sion, especially if performed at a sufficiently early stage.